The impact of curcumin on livestock and poultry animal's performance and management of insect pests - Sureshbabu, Anjana; Smirnova, Elena; Karthikeyan, Adhimoolam; Moniruzzaman, Mohammad; Kalaiselvi, Senthil; Nam, Kiwoong; Goff, Gaelle Le; Min, Taesun (Frontiers in Veterinary Science, 2023)
Plant-based natural products are alternative to antibiotics that can be employed as growth promoters in livestock and poultry production and attractive alternatives to synthetic chemical insecticides for insect pest management. Curcumin is a natural polyphenol compound from the rhizomes of turmeric (Curcuma spp.) and has been suggested to have a number of therapeutic benefits in the treatment of human diseases. It is also credited for its nutritional and pesticide properties improving livestock and poultry production performances and controlling insect pests. Recent studies reported that curcumin is an excellent feed additive contributing to poultry and livestock animal growth and disease resistance. Also, they detailed the curcumin's growth-inhibiting and insecticidal activity for reducing agricultural insect pests and insect vector-borne human diseases. This review aims to highlight the role of curcumin in increasing the growth and development of poultry and livestock animals and in controlling insect pests. We also discuss the challenges and knowledge gaps concerning curcumin use and commercialization as a feed additive and insect repellent.